Decoding artificial intelligence for physicians - Samajdar, Shambo Samrat; Dey, Amit Kumar; Saboo, Bharat (New Delhi: Jaypee Brothers Medical Pub., 2025)
The integration of AI in healthcare is not just a trend; it represents a fundamental shift that redefines how we diagnose, treat, and prevent diseases. From enhancing diagnostic accuracy in radiology to facilitating personalized medicine in oncology and improving chronic disease management through predictive analytics, AI is already playing a critical role in patient$1 (Bs care. Yet, for many physicians, understanding the nuances of AI applications, ethical implications, and integration challenges remains an obstacle. This book seeks to demystify AI for clinicians by providing a structured exploration of AI$1 (Bs current and potential applications across multiple specialties, supplemented with practical case studies, ethical considerations, and regulatory insights.s
Introduction to artificial intelligence in healthcare -- Fundamentals of artificial intelligence: machine learning, deep learning, and natural language processing -- Artificial intelligence in diagnostics -- Personalized medicine and clinical decision support with artificial intelligence -- Artificial intelligence in diabetes and endocrinology -- Artificial intelligence in cardiovascular diseases --Artificial intelligence renal diseases -- Artificial intelligence in ophthalmology -- Artificial intelligence in oncology -- Artificial intelligence in gastroenterology -- Artificial intelligence in neurology -- Artificial intelligence in surgery -- Artificial intelligence in obstetrics and gynecology -- Artificial intelligence in clinical pharmacology and therapeutic drug monitoring -- Artificial intelligence in pediatrics -- Artificial intelligence in biostatistics for clinical practice -- Population health management with artificial intelligence -- Artificial intelligence in enhancing patient education and engagement -- Legal, ethical, and regulatory considerations for artificial intelligence in healthcare -- Implementing artificial intelligence in clinical practice -- Future directions and innovations in artificial intelligence for medicine -- Case studies and real-worls applications of artificial intelligence in healthcare -- Self-assesment - multiple-choice questions (MCQs)
Includes index
Keywords: Artificial Intelligence -- Medical Science